Pemahaman perempuan tentang perubahan iklim di Kabupaten Jember - Raudlatul Jannah; Baiq Lily Handayani; Nurul Hidayat; Akhmad Ganefo (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2023)
Based on data from the Jember Regency Regional Disaster Management Agency (BPBD), in 2019 there were 27 villages experiencing drought. This data continues to increase from year to year even though Jember has several watersheds and is surrounded by mountains and hills with water sources, in fact it has not been able to prevent Jember Regency from drought. This is an irony, especially for Jember Regency which is known for its fertile plantation areas. Environmental damage and the decline in the quality of nature is a reality that cannot be denied. The Aims of the research is to explore the understanding of women in Jember Regency about climate change. Using a survey method, this research was conducted on 140 women in Jember district. This research found that in general women support reducing the rate of climate change but most women do not understand what are the indications of climate change and government initiatives to stop climate change. The majority of women also agree that the role of the media in disseminating climate change is still lacking, so even though women generally hear about climate change, they generally do not understand what climate change is.